Use of topical antipsoriatic drugs in Denmark: a nationwide drug utilization study. (1st January 2019) - Svendsen, M.T.; Ernst, M.S.; Andersen, K.E.; Andersen, F.; Johannessen, H.; Pottegård, A.
Summary: Background: The reported real‐life use of prescribed topical antipsoriatic drugs is conflicting and based on heterogeneous data sources. Objectives: To describe the utilization of topical antipsoriatic drugs among patients with psoriasis in Denmark. Methods: A drug utilization study was performed based on nationwide Danish health registry data. We identified patients who received a first‐time hospital diagnosis of psoriasis and redeemed at least one topical drug prescription in the period 2005–2015 ( n = 7743). Patients were followed for 3 years from the time of diagnosis. Use of topical and systemic antipsoriatic drugs was described, specified by the type of treatment. Results: The total use of topical drugs was divided between corticosteroids with calcipotriol (31%), calcipotriol (6·5%), very potent corticosteroids (24%), potent corticosteroids (30%), moderate corticosteroids (7·2%) and corticosteroids with antimicrobials (1·6%). There was a 19% reduction in the overall use of topical drugs during the study period. Use increased around the time of diagnosis and the majority of patients redeemed more than two packages of topical drugs during the first year after being diagnosed. Regional differences in patients' use of topical drugs varied considerably. The distribution of use of topical drugs was uneven, with a minority of all patients (25%) using 70% of the total amount of topical treatment. There was a 70% increase in the use of methotrexate over the study period. Biologics were used by up to 6%. Conclusions: The study provides further evidence that the use of topical antipsoriatic drugs shows considerable heterogeneity over time and regional practices, and differences between patients.